![Виссарион](https://sproshu.net/uploads/ava/2/ava11439.jpg)
Виссарион
6 год назад
Решите уравнение:
(3x-1)^2-8(x+1)^2 = (x+2)(x-2)
Помогите плиииз!
ОТВЕТЫ
![Карл](https://sproshu.net/uploads/ava/4/ava746.jpg)
Карл
Jun 30, 2019
9х^2-6х+1-8(х^2+2х+1)=х^2 -2х+2х-4
9х^2-6х+1-8х^2-16х-8=х^2-4
-6х-16х=-4-1+8
-22х=3
Х=-3/22
9х^2-6х+1-8х^2-16х-8=х^2-4
-6х-16х=-4-1+8
-22х=3
Х=-3/22
Ответ:
(3x-1)^2-8(x+1)^2=(x+2)(x-2)
9x^2-6x+1-8(x^2+2x+1)=x^2-4
9x^2-6x+1-8x^2-16x-8=x^2-4
x^2-x^2-6x-16x=-4+7
-22x=3
x=-3/22
(3x-1)^2-8(x+1)^2=(x+2)(x-2)
9x^2-6x+1-8(x^2+2x+1)=x^2-4
9x^2-6x+1-8x^2-16x-8=x^2-4
x^2-x^2-6x-16x=-4+7
-22x=3
x=-3/22
252